Association between different stages of precollege school bullying and murder-related psychological behaviors among college students in Anhui Province, China. (December 2019) - Zhang, Guo-Bao; Wang, Geng-Fu; Han, A-Zhu; Xu, Nuo; Xie, Guo-Die; Chen, Li-Ru; Su, Pu-Yu
Highlights: There has been little research on the association between school bullying and murder-related psychological behaviors among adolescents. Murderous ideation and behaviors as a series of psychological possess, including murderous ideation, plans, preparation and attempts were examined. Both primary and secondary school bullying, especially cyber forms, were more likely to have murder-related psychological behaviors among adolescents and a dose-response relationship was found in the current study. Abstract: Little is known about the relationship between precollege school bullying and murder-related psychological behaviors. The present study aims to examine that relationship in Chinese college students using a cross-sectional study. Self-report data were collected from 4034 college students in Anhui Province using a proportional stratified cluster sampling method. Four types of school bullying (i.e., physical, verbal, relational, and cyber) with bullies and victims and two periods (i.e., primary and secondary) were measured. The prevalence rates of murderous ideation, plans, preparation, and attempts were 6.9%, 2.5%, 1.8%, 1.4%, respectively. Different stages of precollege cyber bullying were associated with murder-related psychological behaviors for both bullies (primary: AORs  = 2.78 to 15.67; secondary: AORs =  2.43 to 9.99; both periods: AORs  = 2.26 to 14.04) and victims (primary: AORs  = 2.87 to 16.57; secondary: AORs  = 1.89 to 4.49; both periods: AORs  = 3.68 to 21.48). A dose-response relationship was found, such that college students with a bullying perpetration index of two types and more were more likely to have murder-related psychological behaviors than those who were not bullied. Notably, both primary and secondary school bullying, especially cyber forms, were more likely to be associated with murder-related psychological behaviors. Therefore, it is necessary to develop school bullying preventive measures beginning in primary school.